HUBUNGAN LAMA KERJA DENGAN AKTIVITAS ENZIM ALKALINE PHOSPHATASE (ALP) PADA PETANI DI DAERAH LEMBANG - Fini Ainun Qolbi Wasdili; Cindy Dhea Octaviani; Ayi Furqon (Klinikal Sains : Jurnal Analis Kesehatan, 2022)
Pesticides are chemicals used to poison pests. Farmers in Indonesia use pesticides but many do not understand the rules for using them. The more often farmers are exposed to pesticides, it will have an impact on health problems, liver function disorders, one of the parameters of liver function examination is Alkaline Phosphatase (ALP). The ALP enzyme is an enzyme produced by liver cells and bone-forming cells. This study aims to determine the relationship between length of work and ALP enzyme activity in farmers in the Lembang. The research method used is descriptive and then a One Way ANOVA statistical analysis is carried out to determine the relationship. Data was collected through questionnaires, samples from 22 farmers in Farmer Group X in Cibodas Village, Lembang District, West Bandung Regency, West Java. The average ALP activity of farmers who work 1-5 years is 57 U/I while those more than 5 years are 35 U/I. One Way ANOVA statistical test results obtained a significant value of 0.000 <0.05. The conclusion in this study is that there is a relationship between length of work and ALP activity on farmers in the X Farmer Group